Tasmanian Aboriginal activism and intervention in cultural institutions: repatriation and creating a Pakana museology - Zoe Rimmer (2024)
WARNING: Aboriginal and Torres Strait Islander readers are warned that this thesis may contain references of deceased persons and content which may cause distress The campaign for Trukanini’s skeletal remains to be released from the Tasmanian Museum and Art Gallery (TMAG) so she could be given a respectful, ceremonial farewell in 1976, was critical in advancing the Pakana (Tasmanian Aboriginal) campaign for recognition as a living Community against the prevailing idea of ‘extinction’. This action also helped to instigate the national movement for the repatriation of First Peoples’ Ancestral remains from Australian and overseas collecting institutions, driving changes to institutional and government policies and shaping wider public discourse on these matters. Numerous scholars have examined the history of collecting Pakana Ancestral remains and cultural material; however, there are limited accounts of the Pakana Community’s campaign for their repatriation. Community members have also actively located collections of cultural material and demonstrated how retrieval strengthens cultural knowledge and practice. To date, no singular work brings these connected fields of research together and questions how this knowledge might contribute to First Peoples-led museum practices and policies. This study addresses this gap by investigating how and why repatriation activism has shaped the revival of Pakana cultural identity and the transformation of museology, including curatorial frameworks. Drawing upon my cultural knowledge as a Pakana woman and my experience as a First Nations museum curator, my methodologies are informed by my involvement in, and respectful relationship with, my Community. The research undertaken crosses the disciplines of museum studies, Indigenous studies, and history, and it contributes new knowledge to the related areas of law and anthropology. It follows and extends First Peoples’ research methodologies by privileging Pakana knowledges, in line with the aspirations of the Community, and, while ...